Prenatal Coffin-Siris Syndrome: Expanding the Phenotypic and Genotypic Spectrum of the Disease - Keskinen Sini; Paakkola Teija; Mattila Mirjami; Hietala Marja; Koillinen Hannele; Laine Jukka; Haanpää Maria K (United States, 2025)
Coffin-Siris syndrome is an autosomal dominant disorder with neurological, cardiovascular, and gastrointestinal symptoms. Patients with Coffin-Siris syndrome typically have variable degree of developmental delay or intellectual disability, muscular hypotonia, dysmorphic facial features, sparse scalp hair, but otherwise hirsutism and fifth digit nail or distal phalanx hypoplasia or aplasia. Coffin-Siris syndrome is caused by pathogenic variants in 12 different genes including SMARCB1 and ARID1A. Pathogenic SMARCB1 gene variants cause Coffin-Siris syndrome 3 whereas pathogenic ARID1A gene variants cause Coffin-Siris syndrome 2. Here, we present two prenatal Coffin-Siris syndrome cases with autosomal dominant pathogenic variants: SMARCB1 gene c.1066_1067del, p.(Leu356AspfsTer4) variant, and a novel ARID1A gene c.1920+3_1920+6del variant. The prenatal phenotype in Coffin-Siris syndrome has been rarely described. This article widens the phenotypic spectrum of prenatal Coffin-Siris syndrome with severely hypoplastic right ventricle with VSD and truncus arteriosus type III, persisting left superior and inferior caval vein, bilateral olfactory nerve aplasia, and hypoplastic thymus. A detailed clinical description of the patients with ultrasound, MRI, and post mortem pictures of the affected fetuses showing the wide phenotypic spectrum of the disease is presented.